Students' Learned Helplessness and Teachers' Care in EFL Classrooms - He, Hua (Frontiers in Psychology, 2021)
The construct of learned helplessness, as one of the noticeable emotional issues in education, has been investigated and approved its prominent place in education for its stimulus on students’ accomplishment, enthusiasm, and commitment in learning. Moreover, the role of teachers as the most crucial issues in the learning viewpoint is at the center of attention since they help learners to be more motivated and provide a supportive context by caring. So, the current review of literature tries to emphasize teachers’ care and its effects on decreasing learned helplessness in EFL classrooms. The review of this study underscores the important role of the teachers’ care and support in learners’ improvement of learned helplessness that can be alleviated in this way. Afterward, some suggestions are offered to illuminate the exercise of teachers, learners, teacher trainers, syllabus designers.